Framing Analysis of the Character of Governor and Deputy Governor Candidates in Local Newspapers during the 2018 Regional Election in West Nusa Tenggara - Arzak, Miftahul; Satriadi, Yadi; Safitri, Wahyu Aulia Utami (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the framing of the character of Governor and Deputy Governor candidates in West Nusa Tenggara as presented by three local newspapers during the 2018 regional elections. Employing a qualitative content analysis method grounded in Entman’s framing theory, the research investigates how local media outlets, Suara NTB, Lombok Post, and Radar Lombok, constructed narratives of political figures’ character through four key elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. An analysis of 224 news articles reveals that each candidate pair was framed using different approaches: some were portrayed as experienced leaders, religious figures, intellectuals, populist candidates, successors to previous administrations, or even as champions of ethnic identity. These framings were significantly influenced by the social context and the strategic orientation of the media in building connections between the candidates and specific voter segments. This study affirms that the media do not merely function as conveyors of information but actively construct political realities through the selective creation and emphasis of character based narratives.